2014
DOI: 10.1038/sj.bdj.2014.644
|View full text |Cite
|
Sign up to set email alerts
|

Communication methods and production techniques in fixed prosthesis fabrication: a UK based survey. Part 2: Production techniques

Abstract: Highlights that even though clear guidelines are available, there still seems to be a lack of agreement between dentists and laboratories regarding the disinfection and quality of dental impressions.Despite the promotion of all-ceramic crowns, this survey indicated that metal-ceramic crowns are still the most frequently prescribed for both anterior and posterior restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…It was left to the technician in almost 72.7% of the cases which may affect the ultimate functional and aesthetic outcomes. The results of this study are generally in line with surveys conducted in various regions of the world (Al-AlSheikh, 2012;Aslam & Ahmed, 2015;Avrampou et al, 2012;Berry et al, 2014b;Cotmore, Mingledorf, Pomerantz, & Grasso, 1983;Dickie et al, 2014;Haj-Ali, Al Quran, & Adel, 2012;Radhi et al, 2007;Schwarz & Barsby, 1980).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was left to the technician in almost 72.7% of the cases which may affect the ultimate functional and aesthetic outcomes. The results of this study are generally in line with surveys conducted in various regions of the world (Al-AlSheikh, 2012;Aslam & Ahmed, 2015;Avrampou et al, 2012;Berry et al, 2014b;Cotmore, Mingledorf, Pomerantz, & Grasso, 1983;Dickie et al, 2014;Haj-Ali, Al Quran, & Adel, 2012;Radhi et al, 2007;Schwarz & Barsby, 1980).…”
Section: Discussionsupporting
confidence: 89%
“…However, not all technicians follow this step. Failures in communication between dental office and laboratory lead to a poorly designed prosthesis, jeopardize the success of treatment, and cause tissue damage (Aslam & Ahmed, 2015;Berry, Nesbit, Saberi, & Petridis, 2014a, 2014bDickie, Shearer, & Ricketts, 2014). Moreover, contaminated items or inadequate disinfection of casts or impressions can facilitate the spread of infectious agents and is considered a major threat to the health of treatment team (Abichandani & Nadiger, 2013;Begum, Ahmed, Dithi, Islam, 2013;Alshiddi & Prosthodontics, 2014;Berry et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that 52% of the dental laboratories used base-metal alloy (without further information) as crown material [ 29 ]. In addition, the same authors report that dental laboratories used all-ceramic in 29% of the anterior cases and 8% in the posterior cases [ 29 ]. The same study reported that 8% used high-gold content alloy.…”
Section: Discussionmentioning
confidence: 99%
“…One study examined 1403 impressions submitted to a commercial laboratory in the United States: a majority of the trays used were plastic (62%), and most were dual‐arch (73%) . In a U.K. survey of dentists, 61% used a full‐arch plastic tray for crown impressions . Another U.K. survey reports 65% of impressions used a flexible tray .…”
mentioning
confidence: 99%
“…25 In a U.K. survey of dentists, 61% used a full-arch plastic tray for crown impressions. 26 Another U.K. survey reports 65% of impressions used a flexible tray. 27 While some studies suggest that custom trays or rigid metal trays produce superior impressions, [28][29][30][31] other authors conclude that plastic dual-arch trays, even though less rigid, provide acceptable clinical results.…”
mentioning
confidence: 99%